2008
DOI: 10.1007/s11998-008-9146-0
|View full text |Cite
|
Sign up to set email alerts
|

CdCl2-treated CdTe thin films deposited by the close spaced sublimation technique

Abstract: Cadmium telluride thin films were prepared by the close spaced sublimation (CSS) technique, using CdTe powder as evaporant and were submitted to a chemical treatment at 25°C in a saturated CdCl 2 solution (2.08 g/100 mL methanol), followed by heat treatment under vacuum $10 -3 mbar at 400°C for 30 min. The effect of chemical and thermal treatments on the crystallographic, morphological, optical, and electrical properties were studied through XRD, scanning electron microscope (SEM), spectrophotometry, and dc el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…In this iodine doping experiment in the presence of Cl in the bath, the electrical conductivity increased only by a factor of ~10. Shah et al [48] also reported the electrical resistivity drop by only a factor of ~20 in CdCl 2 -treated CdTe samples grown by CSS method. …”
Section: Variation Of Electrical Conductivitymentioning
confidence: 96%
“…In this iodine doping experiment in the presence of Cl in the bath, the electrical conductivity increased only by a factor of ~10. Shah et al [48] also reported the electrical resistivity drop by only a factor of ~20 in CdCl 2 -treated CdTe samples grown by CSS method. …”
Section: Variation Of Electrical Conductivitymentioning
confidence: 96%
“…With pH increases to 10.5, surface of CdS is decorated and causes this absorbance curve shifting to the long wavelength direction, which indicates that the band gap decreases slightly. Based on the literatures, the decrease of the energy band gap is produced by an increase in the structural disorder induced by the change from cubic to hexagonal phase of CdS [13]. Curve d shows that although absorbance curve has a red shift, the absorption rate is too high after the wavelength 500 nm.…”
Section: Optical Properties Of Cbd Cds Filmsmentioning
confidence: 98%
“…When pH increases to 10.5, surface of CdS is decorated and causes this absorbance curve to shift to the long wavelength direction, which indicates that the band gap decreases slightly. Based on literatures, the decrease of the energy band gap is produced by an increase in the structural disorder induced by the change from cubic to hexagonal phase of CdS [13]. Curve d shows that although absorbance curve has a red-shift, the absorption rate is still high after the wavelength 500 nm.…”
Section: Optical Properties Of Cbd Cds Filmsmentioning
confidence: 92%